Linguistic Errors in Students’ Undergraduate Thesis Background at STAI Miftahul ‘Ulum Tanjungpinang - Dwi Nur Wulandari; Taufik Afdal; Joko Iswanto (Pendidikan Bahasa Inggris (Universitas Internasional Batam), 2021)
Abstract This research was aimed to find out: (1) Types of linguistic errors that students of the English education department of Miftahul ‘Ulum Tanjungpinang commit in writing a thesis, especially in the background section. (2) The most and least dominant linguistic errors were found based on Dulay’s surface strategy taxonomy theory in students of English education department of Miftahul ‘Ulum Tanjungpinang thesis, especially in the background section. This research used a mixed-method (qualitative and quantitative. The qualitative method was used to describe 4 types of linguistic errors based on Dulay’s theory such as addition, omission, misformation, and misordering. While the quantitative method was used to calculate the data include the 4 types of linguistic errors. The data collected in this research were analyzed by using Dulay’s theory and percentage formula. There were 110 students’ theses which were the populations of the data and 10 of them were the samples. The result of the research revealed that there are 128 sentences were contained linguistic errors. The 128 sentences were classified based on 4 types with each presentation. They are addition (11%), omission (30%), misformation (59%), and misordering (1%). Based on the result it can be concluded that misformation was the highest percentage of types of linguistics errors were found in students’ thesis background. Where such errors included subject-verb agreement (31 errors), spelling (18 errors), preposition (14 errors), pronoun (5 errors), capitalization (4 errors), and article (3 errors). Keywords: Error, Linguistic, Linguistic Error, Error Analysis